A Look at Lookism and How It Impacts Pre-Intern Teachers' Expectations - Watkins, Timothy B. (Advances in Social Sciences Research Journal, 2024)
This research was conducted in a small, rural, public university located in the Mississippi Delta with one class of pre-intern teachers. A total of nine pre-interns participated in the study. The purpose of the research was to briefly review the word diversity which causes some of the following terms to come to mind: race, ethnicity, gender, age, religion, physical abilities, mental abilities, income, education, and sexual orientation. However, one dimension of diversity that might not come to mind is appearance - How one looks is how they are judged. Bias based on appearance is known as lookism. This research study was designed using an activity to introduce the pre-intern teachers to the term lookism and how unconscientiously, as teachers, they could make judgements based on the appearance of the students in their future classrooms. The class was divided into small groups of 3 students each to participate in conversation. One discussion prompt focused on the topic, "How prejudice and bias focus on the physical characteristics of people" and the other on "How prejudices and bias focus on the dress and makeup of people." A final whole class discussion was held, and various questions were asked and answered on how a student's appearance might impact pre-intern teachers’ expectations.